Whole genome grey and white matter DNA methylation profiles in dorsolateral prefrontal cortex. Issue 6 (6th February 2017) - Sanchez‐Mut, Jose Vicente; Heyn, Holger; Vidal, Enrique; Delgado‐Morales, Raúl; Moran, Sebastian; Sayols, Sergi; Sandoval, Juan; Ferrer, Isidre; Esteller, Manel; Gräff, Johannes
Abstract: The brain's neocortex is anatomically organized into grey and white matter, which are mainly composed by neuronal and glial cells, respectively. The neocortex can be further divided in different Brodmann areas according to their cytoarchitectural organization, which are associated with distinct cortical functions. There is increasing evidence that brain development and function are governed by epigenetic processes, yet their contribution to the functional organization of the neocortex remains incompletely understood. Herein, we determined the DNA methylation patterns of grey and white matter of dorsolateral prefrontal cortex (Brodmann area 9), an important region for higher cognitive skills that is particularly affected in various neurological diseases. For avoiding interindividual differences, we analyzed white and grey matter from the same donor using whole genome bisulfite sequencing, and for validating their biological significance, we used Infinium HumanMethylation450 BeadChip and pyrosequencing in ten and twenty independent samples, respectively. The combination of these analysis indicated robust grey‐white matter differences in DNA methylation. What is more, cell type‐specific markers were enriched among the most differentially methylated genes. Interestingly, we also found an outstanding number of grey‐white matter differentially methylated genes that have previously been associated with Alzheimer's, Parkinson's, and Huntington's disease, as well as Multiple and Amyotrophic lateral sclerosis. The data presented here thus constitute an important resource for future studies not only to gain insight into brain regional as well as grey and white matter differences, but also to unmask epigenetic alterations that might underlie neurological and neurodegenerative diseases. Abstract : Using whole genome bisulfite sequencing and highthroughput arrays, the authors characterize the DNA methylation patterns of white and grey matter in the prefrontal cortex. Genes differentially methylated were found to be enriched in molecular pathways highly relevant for neuron/glia function and neurodegenerative diseases.